Effect of neutron irradiation on the physicochemical properties of naproxen sodium - D, Sithra; Rahman, Md. Mokhlesur; I, Ibrahim; Awang, Mohamed (Trade Science Inc, 2016)
Abstract Pharmaceutical drug delivery systems for non-steroidal anti-inflammatory drugs involve targeted delivery or controlled release of the drug. The most common method to monitor the in vivo behavior of pharmaceutical dosage form is neutron activation based gamma scintigraphy. It is necessary to ensure that the process of neutron irradiation does not affect the physicochemical properties of the formulated drug and its dosage form. This study, the effect of neutron irradiation on the physicochemical properties of naproxen sodium is investigated and it is also; selected as the model drug. The process of neutron irradiation was carried out at the Malaysian Nuclear Agency using the TRIGA MK II reactor. After irradiation times of 1, 2, 3, 4, 5 and 30 min, the effect of neutron irradiation on physicochemical properties of naproxen sodium was investigated using scanning electron microscope (SEM), gas chromatograph-mass spectrometer (GCMS), Fourier transform infrared spectrometer (FTIR) and ifferential scanning calorimeter (DSC). The physicochemical properties of non-irradiated naproxen sodium were compared to the irradiated naproxen sodium samples. Colour changes after irradiation was observed. Results of analysis of SEM and FTIR spectrometer showed changes in the physicochemical properties of naproxen sodium when duration of irradiation was ncreased. There were no major changes in the result of GC-MS and DSC. Based on the results obtained, it can be concluded that naproxen sodium is a suitable drug that can be used for neutron activation based gamma scintigraphy. The maximum irradiation time that naproxen sodium can withstand without changes in its physicochemical properties is 3 min.